Cytotoxic and cytoprotective effects of tryptamine-4, 5-dione on neuronal cells: a double-edged sword. (4th May 2017) - Suga, Naoko; Murakami, Akira; Nakamura, Yoshimasa; Ishisaka, Akari; Kitamoto, Noritoshi; Ito, Mikiko; Kato, Yoji
Abstract: Serotonin (5-hydroxytryptamine) is a putative substrate for myeloperoxidase, which may convert it into the reactive quinone tryptamine-4, 5-dione (TD). In this study, we found that the viability of human SH-SY5Y neuroblastoma cells treated with 25 μM TD was increased to approximately 117%. On the other hand, the cell viability was significantly decreased by exposure to TD (150–200 μM), with an increase in intracellular reactive oxygen species (ROS). Interestingly, pre-treatment of SH-SY5Y cells with 100 μM TD prevented cell death and suppressed intracellular ROS generation evoked by the addition of hydrogen peroxide (H2 O2 ). Expression of the phase-II antioxidant enzyme NAD(P)H: quinone oxidoreductase 1 and haem oxygenase 1 were upregulated by TD at a concentration of 50–100 μM. Nuclear factor erythroid 2-related factor 2 (Nrf2), the regulator of these enzyme, was translocated from the cytosol to the nucleus by 100 μM TD. In summary, moderate concentrations of TD may increase the self-defence capacity of neuronal cells against oxidative stress.